Changes in Retinal Function and Cellular Remodeling Following Experimental Retinal Detachment in a Rabbit Model. (9th April 2017) - Barliya, Tilda; Ofri, Ron; Sandalon, Shai; Weinberger, Dov; Livnat, Tami
Abstract : Purpose. To explore functional electroretinographic (ERG) changes and associated cellular remodeling following experimental retinal detachment in a rabbit model. Methods. Retinal detachment was created in ten rabbits by injecting 0.1 ml balanced salt solution under the retina. Fundus imaging was performed 0, 3, 7, 14, and 21 days postoperatively. ERGs were recorded pre- and 7 and 21 days postoperatively. Eyes were harvested on day 21 and evaluated immunohistochemically (IHC) for remodeling of second- and third-order neurons. Results. Retinal reattachment occurred within two weeks following surgery. No attenuation was observed in the photopic or scotopic a- and b-waves. A secondary wavefront on the descending slope of the scotopic b-wave was the only ERG result that was attenuated in detached retinas. IHC demonstrated anatomical changes in both ON and OFF bipolar cells. Bassoon staining was observed in the remodeled dendrites. Amacrine and horizontal cells did not alter, but Muller cells were clearly reactive with marked extension. Conclusion. Retinal detachment and reattachment were associated with functional and anatomical changes. Exploring the significance of the secondary scotopic wavefront and its association with the remodeling of 2nd- and 3rd-order neurons will shade more light on functional changes and recovery of the retina.